2015
DOI: 10.1080/10910344.2015.1018534
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Abrasive Types on Grinding of Chopped Strand Mat Glass Fiber-Reinforced Polymer Composite Laminates

Abstract: 2 A grindability study of chopped strand mat glass fiber reinforced polymer laminates (CSM GFRP) has been carried out to evaluate the effects of abrasive types on grinding force ratio and area roughness at varying grinding parameters such as speed, feed and depth of cut. Performances of alumina (Al 2 O 3 ) and cubic boron nitride (CBN) wheels were compared. Both wheels delivered the maximum grinding force ratios at low speed, high feed and low depth of cut. Alumina wheel produced smoother surface when grinding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Chockalingam et al 2,18 evaluated the effects of tool abrasive types on force and roughness when grinding GFRP at varying conditions. Performances of cubic boron nitride (CBN) abrasives was specially investigated and compared to alumina (Al 2 O 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chockalingam et al 2,18 evaluated the effects of tool abrasive types on force and roughness when grinding GFRP at varying conditions. Performances of cubic boron nitride (CBN) abrasives was specially investigated and compared to alumina (Al 2 O 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…One is the pit formed by the protruding fiber bundle under the action of digging up during grinding, and the other is the expansive bulge composed of uncut glass fibers. Chockalingam et al [81] showed that the protruding fibers are still obvious in GFRP dry grinding, although the surface is covered with broken matrix. The surface ground with synthetic coolant is clean, hard, and smooth.…”
Section: Materials Removal Mechanismmentioning
confidence: 99%
“…In [ 55 ], the grinding of chopped strand mat (CSM) GFRP laminates was investigated to evaluate the effects of abrasive types, alumina (Al 2 O 3 ), and cubic boron nitride (CBN), on the grinding force ratio and surface roughness under various cutting parameters, such as speed, feed, and depth of cut. For both abrasive types, the maximum grinding force ratio was found at low speed, high feed, and low depth of cut.…”
Section: Conventional Machining Processesmentioning
confidence: 99%